Cardioneuroablation for successful treatment of symptomatic bradycardia in a 12-year-old child after a 6-month follow-up - Xu, Xin; He, Shuang; Liu, Qian; Liu, Ruixi; Zhang, Lei; Chen, Weijie; Yin, Yuehui; Lu, Tiewei (Frontiers in Cardiovascular Medicine, 2023)
Background:Cardioneuroablation (CNA) is recognized as a promising therapeutic option for adults with severe symptomatic bradycardia due to excessive vagal tone. however, no pediatric cases have been reported to date. The aim of this study is to evaluate the feasibility and efficacy of CNA in children.A 12-year-old male patient was hospitalized with symptoms of fatigue, palpitations and syncope for more than 2 months who was definitively diagnosed with functional sinoatrial node dysfunction by 12-Lead-electrocardiogram，24h-holter monitoring , loading dose of atropine test(0.04mg/kg) and treadmill exercise test.meanwhile, whole-exome sequencing (WES)was performed on the child and his core family members, After completing the preoperative examination and signing the informed consent form, the child underwent CNA therapy. Results: After the electroanatomic structure of both atria was mapped out by the Carto 3 system, according to the protocol of purely anatomy and local fractionated intracardiac electrogram guided-CAN methods, The local fractionated intracardiac electrograms of each cardiac ganglionated plexus (GPs) including Ao-SVC GP, PMLGP, RAGP, LSGP, RIGP and LIGP were used as targets for ablation at a power of 30 W with an ablation index of 350-400. At a 6-month follow-up, the child's heart rhythm completely restored to sinus rhythm and clinical symptoms disappeared.The application of CNA in a child with symptomatic sinus bradycardia was first achieved with better clinical outcomes. The CNA can be carried out cautiously in children under suitable indications.